Toward, With, and From a Fourth World (Fourth World Journal, 2025)
This article examines Fourth World theory through multiple lenses, focusing on its relevance to distressed urban spaces, Indigenous self-governance, technology, and anti-colonial praxis. It critically assesses foundational assumptions and suggests theoretical expansions, underscoring the centrality of Indigenous perspectives and self-determination. Key themes include structural and cultural contributors to urban distress, the concept of ‘Home Rule’ as Indigenous political autonomy, and the inseparability of land, culture, identity, and governance. The discussion highlights the deep connections between Indigenous peoples and their ancestral territories, emphasizing the indivisible nature of land and cultural identity. Furthermore, the article advocates for anti-colonial theorization and resilience through Indigenous resistance to colonial systems. By integrating diverse geographic and cultural contexts, including Gary, Indiana, and the Shuswap Nation, the work advances understanding of Fourth World struggles and political acts in research grounded in Indigenous worldviews.